2021
DOI: 10.24874/ti.1014.11.20.02
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Oil based Biodegradable Refrigeration Oil - An Optimization of Tribological Characteristics Using D-optimal Design

Abstract: The present study investigates the tribological behaviour of vegetable oilbased polyolester refrigeration oil using the pin-on-disc tribometer. Experiments were carried out choosing the load and sliding velocity as a function of rotational speed as the numerical factor and refrigeration oil as the categorical factor. Response surface methodology (RSM) based Doptimal design was utilized for modelling and optimization of friction and wear characteristics. The tribological characteristics of a lubricantmaterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In literature [19], sliding velocity was investigated to impact the tribological performance of refrigerants and the study inferred that if increasing sliding velocity, the lubricant entrainment also increases along with lubricant film thickness. Vithya et al [20] checked the tribological properties of polyolester refrigeration oil under different load conditions and found that COF decreases based on the applied load. In this background, the author chose the concentration of graphene nanoparticles in POE oil, sliding velocity, and the applied load as experimental factors.…”
Section: Introductionmentioning
confidence: 99%
“…In literature [19], sliding velocity was investigated to impact the tribological performance of refrigerants and the study inferred that if increasing sliding velocity, the lubricant entrainment also increases along with lubricant film thickness. Vithya et al [20] checked the tribological properties of polyolester refrigeration oil under different load conditions and found that COF decreases based on the applied load. In this background, the author chose the concentration of graphene nanoparticles in POE oil, sliding velocity, and the applied load as experimental factors.…”
Section: Introductionmentioning
confidence: 99%